ANALISIS BUDAYA ORGANISASI (STUDI KASUS PADA KOPERASI CREDIT UNION KASIH SEJAHTERA ATAMBUA) - Marianus S Neno (Journal of Management Small and Medium Enterprises (SMEs), 2019)
Culture organization is a batch of key characteristic which is respected by an organization. Those key characteristics formed a “communal meaning” to become the genuine of the organization (Robbins: 2008). The main goal of this thesys is to know how the cultural organization’s of “Credit Union Kasih Sejahtera Atambua”. The analysis of methode which is used here is Descriptive Statistic Analysis. The datas collected by spreading quistioners to the respondents. Those data which is collected will be proccess by some phases, editing, coding, scoring, and tabulating. Those datas will be analysed by using mean. The result of analysis shows an illustration that “Credit Union Kasih Sejahtera Atambua” has cultural creativity, initiative, carefullness, innovative and spirit of group working. The main problem which is must to be noticed is discipline of the workers. Besides, the courage, patience, sensitivity, and motivation of the workers must be noticed too. Keyword : Cultural Organization